Do Only White or Asian Males Belong in Genius Organizations? How Academic Organizations’ Fixed Theories of Excellence Help or Hinder Different Student Groups’ Sense of Belonging - Bauer, Christina; Hannover, Bettina (Frontiers in Psychology, 2021)
High-profile organizations often emphasize innate, fixed giftedness rather than malleable effort-based criteria as critical for excellent achievements. With giftedness being primarily associated with White or /Asian males, such organizational implicit theories of excellence may shape individuals’ sense of belonging depending on the extent to which they match the gifted White/Asian male prototype, i.e., the prototypical gifted person which is typically imagined to be a White or Asian male. Previous research has reported fixed (vs. malleable) excellence theories emphasizing giftedness (vs. malleable theories emphasizing effort) to impair the sense of belonging of females and negatively stereotyped ethnic minorities. We investigate the combined effects of gender and ethnicity. We predicted that, while individuals whose gender and ethnicity do not match the gifted prototype show a reduced sense of belonging in fixed organizations, White/Asian males who match the gifted prototype show the opposite effect, experiencing a higher sense of belonging in fixed (vs. malleable) organizations. In an experimental study (N=663 students), we manipulated advertising material used by a highly selective academic institution in Germany and tested effects on students’ belonging. Whereas the original material emphasized giftedness as essential for excelling (fixed excellence version), our manipulated version stressed effort (malleable version). As expected, females from stereotyped ethnic minority groups felt less belonging in the fixed (vs. malleable) organization, while White/Asian males anticipated stronger belonging in the fixed (vs. malleable) organization. Fixed views of excellence impair negatively stereotyped individuals’ belonging but may even strengthen the belonging of prototypical academic elites.